Death and Sexuation in Early Modern Age: The Absence of Macabre and Sexual Difference Construction in Women’s Tombstones in Alcalá de Henares and Lisbon - Aguilar Salinas, Marina (Eikón / Imago, 2021)
The present article proposes a comparative study of the gravestones of the city of Alcalá de Henares and of Museo do Carmo in Lisbon. In their epigraphy, written representations can be found under the form of mentions, names and surnames, and various allusions to the women who were buried there. These women, members of the social elite, possessed the privilege of being buried within the temples. A search of the absence of macabre symbols which do appear, nevertheless, in some masculine gravestones of the same context, opens the way to the formulation of a hypothesis about gender difference. This hypothesis could be denied in some other cases in Spain and England but is confirmed in this present double source. In future investigations we hope to increase this source